(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the possibilities of effectively using modern educational technologies in organizing English language lessons. The study examines the role of information and communication tools, interactive methods, and online platforms in enhancing learners’ engagement in language learning. It also analyzes methodological approaches that foster creativity, independent thinking, and the development of communicative skills. The findings suggest that the rational use of new technologies significantly increases the effectiveness of the English language learning process.